An Innovative Assessment of the Dynamics of Facial Movements in Surgically Managed Unilateral Cleft Lip and Palate Using 4D Imaging. (September 2020) - Gattani, Shyam; Ju, Xiangyang; Gillgrass, Toby; Bell, Aileen; Ayoub, Ashraf
Objective: Assess facial asymmetry during maximum smile in patients with surgically managed unilateral cleft lip and palate (UCLP), using a dynamic 3-dimensional (3D) imaging (4-dimensional) system. Design: Prospective 2 cohort comparative study. Methods: Twenty-five surgically managed UCLP cases and 75 controls at 8 to 10 years of age were recruited. Facial movements during maximum smile were recorded using video stereophotogrammetry at a rate of 60 3D facial images per second. Maximum smile took approximately 3 seconds and generated 180 3D facial images for the analysis. A generic facial mesh which consists of more than 7000 quasi landmarks was used for the assessment of facial asymmetry at 5 key 3D frames representing the pattern of maximum smile. Results: Statistically significant differences were seen regarding the magnitude of facial asymmetry between the UCLP group and the noncleft controls. Higher average asymmetry in the UCLP group was seen in the 3D frame midway between maximum smile and rest (frame 4) followed by the frame at peak expression of maximum smile (frame 3). The average magnitude of nasolabial asymmetry of the control group was within 0.5 mm in comparison with the UCLP cases which was about 1.8 mm. Conclusion: This study provided for the first time, an objective tool for analysis of the dynamics of muscle movements which provided an unprecedented insight into the anatomical basis of the residual dysmorphology. The research demonstrates the limitations of the primary lip repair in achieving symmetrical results and underpins the required refinements to improve the quality of surgical repair of cleft lip.